Duties of educators and administrators in adapting immigrant students to school - Mustafa, Kabatas (Academic Journals, 2021)
In this study, the roles of teachers and school administrators in the adaptation of immigrant students to the school organization were investigated. For this purpose, the opinions of teachers and school administrators were taken for the adaptation of immigrant students to the school organization. The interview form used in the research was created by the researcher with the help of field experts. Participants consist of schools with a large number of immigrant students. The data obtained using face to face interview method was analyzed by content analysis technique. The research data were themed as studies on the adaptation of immigrant students to school, the adaptation and academic problems of immigrant students at school, and the solution of the problems encountered in the adaptation of immigrant students to school. Solution suggestions were tried to be found. As a result, there are important problems in the education of immigrant students. It may be suggested to plan serious activities in order to support teachers with in-service trainings on the education of immigrant children, to monitor students' attendance at school, and to eliminate communication problems between immigrant students and other students.   Key words: Quality education, immigrant students, school, right to education, educational adaption.
Keywords: 4. Education; 8. Economic growth; 16. Peace & justice; 10. No inequality; 3. Good health